[OP.7A.05] SLEEP DISTURBANCES AND RESISTANT HYPERTENSION IN A LARGE SAMPLE OF TREATED HYPERTENSIVE SUBJECTS – POL-FOKUS STUDY. (September 2017) - Talarowska, P.; Klocek, M.; Gasowski, J.; Szelenberger, W.; Wolf, J.; Piotrowski, T.; Piotrowska, A.; Topor-madry, R.; Lesniak, W.; Czarnecka, D.; Kawecka-jaszcz, K.; Narkiewicz, K.; et al.
Abstract : Objective: To evaluate the relationship between sleep disorders (obstructive sleep apnoea (OSA) and insomnia) or sleep habits (short sleep duration) and prevalence and characteristics of resistant hypertension (RHT). Design and method: In a sub-study of the cross-sectional questionnaire-based observational Pol-Fokus study we included 3477 (mean age 62.6 +/− 12.7 years; F 57.8%, M 42.2%) hypertensive patients attending a routine visit. To be included patients had to be >18 years old and had to be treated for at least 12 months with antihypertensive drugs. We defined hypertension control as office blood pressure (BP) levels both <140 mmHg/<90 mmHg. Patients were divided into 3 groups: controlled hypertension, uncontrolled hypertension (not fulfilling the criteria of RHT) and RHT (uncontrolled hypertension despite using 3 antihypertensive drugs including diuretic). High risk of OSA was assessed on the basis of STOP-Bang questionnaire results. Insomnia was evaluated by means of Athens Insomnia Scale (AIS) and the patients with AIS score of 8 or more points were labeled as insomniacs. Short sleep duration was defined as declared usual sleep time <6 hours (for the past 6 months). Results: In the studied group both uncontrolled hypertension and RHT were more frequent among patients with high risk of OSA (28.7% and 28.8% vs. 25.1% and 19.1%; p < 0.001), insomnia (28.5% and 26.5% vs. 25% and 20%; p < 0.001) or short sleep time (27.4% and 30.2% vs. 26.2% and 21.1%; p < 0.001) than in patients without those conditions. Among patients with RHT, high risk of OSA (43.7% vs. 31.1%; p < 0.001), insomnia (41.2% vs. 32.7%; p < 0.001) and short sleep time (17.1% vs. 11.3%; p < 0.001) were more frequent than in patients without RHT. A multivariate model which included sleep disturbances showed that both high-risk OSA and insomnia were also related to the presence of RHT (OR = 1.38; 95%CI 1.10–1.72; p = 0.005; and OR 1.32; 95%CI 1.06–1.65; P = 0.014; respectively), which was not evident for short sleep time. Conclusions: Our results showed that sleep disturbances – high risk of OSA, insomnia and short sleep time - are related to uncontrolled and resistant hypertension. Moreover high risk of OSA and insomnia independently predicted presence of resistant hypertension.